CONSORT extension for reporting N-of-1 trials for traditional Chinese medicine (CENT for TCM) : Recommendations, explanation and elaboration. (October 2019) - Li, Jiang; Hu, Jia-yuan; Zhai, Jing-bo; Niu, Jun-qiang; Kwong, Joey S.W.; Ge, Long; Li, Bo; Wang, Qi; Wang, Xiao-qin; Wei, Dang; Tian, Jin-hui; Ma, Bin; et al.
Highlights: This CONSORT extension for reporting N-of-1 trials for traditional Chinese medicine (CENT for TCM) is the first reporting guidance for N-of-1 trials using traditional Chinese medicine. Based on the CONSORT extension for reporting N-of-1 trials (CENT 2015), 8 items were revised and elaborated, item 1, 2, 4, 5, 6, 11, 12 and 21, for combining with the diagnostic and therapeutic specificity of TCM. We added the new sub-item 1c, keywords, to clarify the trial type and TCM interventions. In item4a, we emphasized that there should be a diagnosis of TCM syndrome of the participants. In item5, we respectively elaborated the different TCM interventions and suggested using the existing standard, CONSORT-CHM FORMULAS 2017 and STRICTA 2010. We would disseminate CENT for TCM and encourage clinical researchers who conduct N-of-1 trials of TCM to use the checklist with the design, implementation and reporting of their trials. Abstract: Background: N-of-1 trial is a desired and appropriate approach to assessing the efficacy and safety of traditional Chinese medicine (TCM) interventions. There have been an increasing number of N-of-1 trials for TCM published. However, a lack of preferred reporting guidance led in the general poor reporting quality of these trials. Due to the unique characteristics of TCM, the working group developed this CONSORT Extension for reporting N-of-1 Trials for Traditional Chinese Medicine (CENT for TCM) to assist TCM researchers in reporting N-of-1 trials for TCM. Methods: We registered CENT for TCM at the EQUATOR (Enhancing the QUAlity and Transparency Of health Research) Network (available at equator-network.org). The development was a comprehensive process through collection of the initial reporting items, two-round scientific Delphi consensus survey with 17 panelists, revision and formation of the final reporting checklist. Results: The checklist includes 25 items within six domains, eight items in which were extended and elaborated on the items of the CENT 2015 checklist. Explanation of the items were listed adequately considering the nature of TCM, introducing the concept of TCM syndrome differentiation and TCM interventions. Conclusions: CENT for TCM can be used to assess the completeness of the reporting of N-of-1 trials for TCM. The working group expect that CENT for TCM could be a practical tool to enhance the comprehensiveness and transparency of the design, implementation and reporting of N-of-1 trials for TCM.